2007
DOI: 10.1002/hep.21901
|View full text |Cite
|
Sign up to set email alerts
|

Terlipressin improves renal function in patients with cirrhosis and ascites without hepatorenal syndrome

Abstract: Patients with advanced cirrhosis and ascites are characterized by circulatory dysfunction with splanchnic vasodilatation and renal vasoconstriction, which often lead to ascites. The vasoconstrictor terlipressin improves renal function in hepatorenal syndrome (HRS). The aim of this study was to evaluate if terlipressin also improves renal function in patients with ascites without HRS. Twenty-three patients with cirrhosis participated; 15 with nonrefractory ascites were randomized to either terlipressin (N group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
98
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 38 publications
5
98
1
1
Order By: Relevance
“…The decrease in plasma sodium is the reflection of terlipressin's ability to retain water as shown in this study and to induce natriuresis as previously shown (9). In studies in HRS terlipressin has been shown to improve plasma sodium, however, only in combination with albumin (18,25).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The decrease in plasma sodium is the reflection of terlipressin's ability to retain water as shown in this study and to induce natriuresis as previously shown (9). In studies in HRS terlipressin has been shown to improve plasma sodium, however, only in combination with albumin (18,25).…”
Section: Discussionsupporting
confidence: 73%
“…This suggests that the V 2 receptor stimulation was intense, which corresponds with the observed increase in AQP2 excretion and in absolute distal water reabsorption. In contrast, terlipressin increases sodium excretion without affecting the distal sodium reabsorption (9).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[1][2][3][4]7 This treatment causes a marked increase in GFR in approximately 50% of patients and improves survival in type 1 HRS. [8][9][10][11][12] Therefore, this pharmacological treatment has become the standard of care for this condition. 13 Nonetheless, it is important to remark that short-term mortality remains elevated despite reversal of type 1 HRS and that liver transplantation (LT) remains the definitive therapy in candidate patients.…”
mentioning
confidence: 99%
“…Vasoconstrictors such as the α1-adrenergic agonist midodrine or terlipressin improve circulatory and renal function in patients with and without refractory ascites. Terlipressin is given in intravenous boluses (1 mg at onset of paracentesis, 1 mg at 8 h and 1 mg at 16 h) in addition to oral midodrine (for 72 h post-paracentesis), which appear to be as good as albumin in suppressing plasma renin elevation in randomized trials; terlipressin is not commercially offered in the United States [51,68,69].…”
Section: Other Treatment Optionsmentioning
confidence: 99%